MDCT evaluation of coronary artery calcification in Nepalese population undergoing CT thorax examination for non-cardiac pathology - Gupta, Mukesh Kumar; Rauniyar, Raj Kumar; Pandey, Naveen Kumar; Yadav, Deepak Kumar (Asian Journal of Medical Sciences, 2014)
Background:Coronary artery calcification (CAC) is frequently encountered as incidental findings during CT evaluation of thorax; however, little is known about its magnitude and association with atherosclerotic risk factors in Nepalese population. The purpose of this study was to evaluate the frequency of incidental CAC in patients undergoing standard thoracic CT examination for non-cardiac pathology and to correlate it with risk factors for coronary atherosclerosis. Methods: A hospital based prospective cross-sectional study was conducted on 216 patients over 8 month duration. The coronary arteries were evaluated for calcification on 16-slice MDCT and the frequency of CAC was correlated with atherosclerotic risk factors viz. age, sex, diabetes mellitus, hypertension, smoking and obesity. Results: Incidental CAC was seen in 72(33.3%) of total 216 patients. The rates of CAC below 40, 40-60 and above 60 years age group were 0%, 31.6% and 43.9% respectively. The frequency of CAC in male and female were 35% and 31.2% for all ages, 43.6% and 20% for 40-60 years group, and 35.2% and 61.1% for above 60 years age group respectively. The frequency of CAC was higher in patients with diabetes mellitus (47.5%), hypertension (42.3%), smoking (43%) and obesity (38.9%). Conclusion: Incidental CAC was seen in 33.3% of the patients and it had significant association with advancing age, diabetes mellitus, hypertension and smoking. Rate of CAC was significantly higher in male for 40-60 years group but the frequency drastically increased in female for above 60 years group. DOI: http://dx.doi.org/10.3126/ajms.v6i4.11205 Asian Journal of Medical Sciences Vol.6(4) 2015 40-44